Prospective evaluation of flow cytometric characteristics, histopathologic diagnosis and clinical outcome in dogs with naïve B‐cell lymphoma treated with a 19‐week CHOP protocol. (25th November 2019) - Wolf‐Ringwall, Amber; Lopez, Lynelle; Elmslie, Robyn; Fowler, Brooke; Lori, Janet; Sfiligoi, Gabriella; Skope, Anne; Arnold, Erin; Hughes, Kelly L.; Thamm, Douglas H.; Ehrhart, E. J.; Avery, Anne C.; et al.
Abstract: Canine B‐cell lymphoma is a clinically heterogenous disease; however, it is generally treated as a single disease entity. The purpose of this clinical trial was to prospectively evaluate naïve canine B‐cell lymphoma patients using histopathology, flow cytometry (FC) and a standardized chemotherapy protocol to better define subsets of this disease that may respond differently to treatment. Sixty‐four dogs with naïve multicentric B‐cell lymphoma were treated with a standardized 19‐week CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) chemotherapy protocol. Most of the dogs (84.3%) were diagnosed with diffuse large B‐cell lymphoma (DLBCL), followed by nodal marginal zone (7.8%), small B‐cell (4.7%), Burkitt‐like (1.6%) and follicular lymphoma (1.6%). FC confirmed the diagnosis of B‐cell lymphoma in all cases. There were no clear phenotyping differences between the subtypes of B‐cell lymphoma detectable by our FC panel. The histologic subtypes in this study exhibited a range of forward scatter values on flow cytometry, but all of the DLBCL cases were higher than a value of 469, while the only cases with a lower forward scatter value were follicular lymphoma and diffuse small B‐cell lymphoma. Dogs with DLBCL had a significantly better objective response rate to the CHOP protocol (96.3%) than the non‐DLBCL subtypes (70%, P = .024). The median progression‐free survival time for patients with DLBCL (233 days) was significantly longer than that of all other histopathologic subgroups combined (163 days, P = .0005).